INTERNAL AND EXTERNAL DETERMINANTS OF ISLAMIC COMMERCIAL BANK LIQUIDITY - Fadhilah Nur Afifa (Program Studi Magister Ekonomi Syariah UIN Ar-Raniry, 2025)
This quantitative study examines the impact of internal and external factors on the liquidity of Indonesian Islamic Commercial Banks (BUS) from 2019 to 2023. This research is crucial as Islamic banks face liquidity risks threatening their operational sustainability, necessitating effective risk management. The application of this research can help develop liquidity strategies. Financing to Deposit Ratio (FDR) serves as the dependent variable, while Non-Performing Financing (NPF), Capital Adequacy Ratio (CAR), Gross Domestic Product (GDP), and inflation comprise the independent variables. Multiple linear regression analysis of quarterly time-series data from OJK, BPS, and Bank Indonesia reveals significant simultaneous effects of NPF, CAR, GDP, and inflation on FDR. Specifically, NPF exhibits a positive, significant effect, whereas CAR's effect is positive but insignificant. GDP demonstrates a negative, insignificant effect, and inflation has a positive, significant impact on FDR.